Analisis Pendapatan, Biaya Dan Sisa Hasil Usaha (SHU) Pada Koperasi Karyawan Nusa Tiga Unit PISMK - Afdillah Nur Aisyah Sinaga; Muhammad Irwan Padli Nasution (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to analyze the income, costs and residual operating results (SHU) in the Nusa Tiga PISMK Employee Cooperative. The research method used is a qualitative research method with a descriptive method. The data in this study is the development of SHU from 2019-2021 and the financial statements of the Nusa Tiga Employee Cooperative PISMK Unit. Meanwhile, the source of data in this study is the Nusa Tiga Employee Cooperative PISMK Unit. The results showed that the income n followed by the annual cost also increased causing the Remaining Operating Income (SHU) to also increase.